How do you evaluate (2g - 1) ^2 - 2g + g ^2 for g = 3? Algebra Expressions, Equations, and Functions Variable Expressions 1 Answer Shwetank Mauria Mar 25, 2017 For g=3, we have (2g-1)^2-2g+g^2=28 Explanation: Putting g=3 in (2g-1)^2-2g+g^2, we get (2xx3-1)^2-2xx3+3^2 = (6-1)^2-6+9 = 5^2+3 = 25+3 = 28 Answer link Related questions How do you write the variable expression for: a quotient of 2 and the sum of a number and 3 ? What are variables? What are variable expressions? How do you write variable expressions? How do you evaluate variable expressions? How do you simplify the expression 3x-x+4? How do you write a quotient of a number and 6 as an expression? How do you evaluate the expression 2x+1 for x=1? How do you write a product of a number and 2 as an expression? How do you write 5 less than 2 times a number as a variable expression? See all questions in Variable Expressions Impact of this question 1295 views around the world You can reuse this answer Creative Commons License